EMOTIONALLY INTELLIGENT STORYTELLING THROUGH AI AND ML USING EMOTIONAL ARCS OF MOTION PICTURE THAT RESONATE WITH AUDIENCES: EMOTIONALLY INTELLIGENT STORYTELLING THROUGH AI AND ML - Prashanth Ramappa (Global journal of Business and Integral Security, 2024)
Film and moviemaking production are an intricate process, mainly decision-making among its producers, Motion picture directors, and writers, especially for script selection. Movie or Filmmaking is a huge investment, it takes more of a resource of Capital, Manpower & Creativity. Traditional script evaluation methods: almost entirely subjective measurements; reliant on the vast and varied experiences of industry professionals (style) — thus inevitably creates bias disparities in decision making, often discounting new or unique narratives. Film producer should be clear whether the narrative is appropriate for the audience’s typical emotional journey. Understanding emotions in scripts is a difficult and complicated task. Our Approach involved, combined the concept of Shapes of stories, Emotional Analysis using Natural Language Processing (wheel of emotion) and ML Clustering technique to solve challenge. Our Methodology involves the use of subtitle data to demystify the emotions in the story. We also apply NRCLex, a lexicon-based method, to associate with eight basic emotions and cluster similar movies within the six main story shapes. Our findings indicate that stories generally follow the six fundamental forms. We also found that movies in the "Man in the Hole" category where the hero faces an unexpected challenge, overcomes his fear, and succeeds in becoming a leader have the highest box office and popularity success.